Intra- and inter-industry productivity spillovers in OECD manufacturing: a spatial econometric perspective - Harald Badinger; Peter Egger (Center for Economic Studies and ifo Institute (CESifo), 2008)
We adopt a spatial econometric approach to estimate intra- and inter-industry productivity spillovers in total factor productivity transmitted through input-output relations in a sample of 13 OECD countries and 15 manufacturing industries. Both R&D spillovers as well as remainder, input-output-related linkage effects are accounted for, the latter of which we model by a spatial regressive error process. We find that knowledge spillovers occur both horizontally and vertically, whereas remainder spillovers are primarily of intra-industry type. Notably, these intra-industry remainder spillovers turn out economically more significant than R&D spillovers.
Keywords: L60; C21; F14; 330; intra-industry spillovers; inter-industry spillovers; productivity; spatial econometrics; research and development; Produktivität; Spillover-Effekt; Input-Output; Schätzung; Verarbeitendes Gewerbe; OECD-Staaten